2021
DOI: 10.1124/jpet.121.000719
|View full text |Cite
|
Sign up to set email alerts
|

The Dopamine D1 Receptor Positive Allosteric Modulator Mevidalen (LY3154207) Enhances Wakefulness in the Humanized D1 Mouse and in Sleep-Deprived Healthy Male Volunteers

Abstract: Dopamine (DA) plays a key role in several central functions including cognition, motor activity and wakefulness. While efforts to develop D1 receptor agonists have been challenging, a positive allosteric modulator (PAM), represents an attractive approach with potential better drug-like properties. Our previous study demonstrated an acceptable safety and tolerability profile of the D1 PAM mevidalen (LY3154207) in single and multiple ascending dose studies in healthy volunteers (Wilbraham et al., 2020). Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Mevidalen improved motor function in patients with Lewy Body Dementia when given in addition to standard dopaminergic therapy (Biglan et al, 2021 ), and initial findings also hint at a possible alleviation of motor symptoms in Parkinson's Disease patients (Wilbraham et al, 2021b ). Mevidalen was also reported to increase wakefulness in both sleep-deprived mice and human subjects (McCarthy et al, 2021 ).…”
Section: Introduction To D1r Pharmacologymentioning
confidence: 99%
“…Mevidalen improved motor function in patients with Lewy Body Dementia when given in addition to standard dopaminergic therapy (Biglan et al, 2021 ), and initial findings also hint at a possible alleviation of motor symptoms in Parkinson's Disease patients (Wilbraham et al, 2021b ). Mevidalen was also reported to increase wakefulness in both sleep-deprived mice and human subjects (McCarthy et al, 2021 ).…”
Section: Introduction To D1r Pharmacologymentioning
confidence: 99%
“…The efficacy of pimavanserin and AVN-211 are currently being intensively investigated in large clinical trials. The search for a suitable intervention within the dopaminergic system away from D 2 /D 3 antagonism also continues, but so far without unequivocal evidence of sufficient effectiveness [225][226][227][228][229][230][231][232][233][234][235][236][237].…”
Section: Discussionmentioning
confidence: 99%
“…The D 1 receptor shows relatively high expression in mesocortical projections to the prefrontal cortex, a brain area of key importance for higher cognitive functions, including working memory, attention, and executive function [ 223 , 224 ]. After promising preclinical investigations, the central acting and potent D 1 -receptor PAM mevidalen (LY-3154207) has been investigated in human studies and showed acceptable safety and tolerability [ 223 ] as well as positive effects on enhancing wakefulness in in sleep-deprived healthy volunteers [ 225 ]. The substance was investigated for the treatment of cognitive deficits in Lewy body dementia and Parkinson’s disease (NCT03305809), where it improved motor symptoms but had no beneficial effects on cognition [ 226 ].…”
Section: Novel Approaches Targeting the Dopaminergic Systemmentioning
confidence: 99%
“… 92 In addition, a recent study revealed that mevidalen, the dopamine D1 receptor positive allosteric modulator, can contribute to prolonged MSL measured by MSLT and enhance wakefulness in healthy sleep-deprived healthy volunteers. 93 As previously discussed, however, most D2 receptor agonists, including pramipexole and ropinirole, could induce EDS in PD patients. Accordingly, divergent affinity for D1 and D2 receptors could result in different effects on EDS of dopaminergic drugs, which is associated with the activities of striatal neurons.…”
Section: Etiology and Pathophysiological Mechanisms Of Eds In Pdmentioning
confidence: 93%
“…Several studies showed that dopamine D1 receptor agonist promoted wakefulness while D2 receptor agonist increased sleep. 92 , 93 Based on relevant literature, divergent dose-dependent effects of DA agonists in healthy subjects vs PD patients may be related to the imbalance of D1 receptor and D2 receptor activity. That is to say, relatively hyperactivated D2 receptor due to the loss of D1 receptor or increased D2 receptor expression in PD could lead to sleepiness when using dopaminergic agents.…”
Section: Etiology and Pathophysiological Mechanisms Of Eds In Pdmentioning
confidence: 99%